Current awareness program of Saint Louis University Library an assessment based on users' perceptions - Diaron, Rina H.; Sison, Josephine C.; Quiros, Edgardo B. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 2003)
The study looked into the methods of current awareness services being employed in Saint Louis University Library as perceived by the library users composed of the non-teaching personnel, faculty members, and students. It also looked into the basic requirements of the different methods of current awareness services and the various perceptions of library users with regard to the availability of current awareness services as an alerting service. The descriptive method was used with the survey questionnaire and unstructured interviews as the research instruments. The respondents of the study included seven (7) non-teaching personnel, thirteen (13) faculty members, seventeen (17) graduate students, and three hundred fifty-eight (358) undergraduate students. Int eh interpretation of data, the weighted mean was used.
Based on the findings of the study, the following conclusions were drawn: (1) Bulletin boards play an important role in extending the level of current awareness services; (b) Methods of current awareness services are not widely read nor scanned by library users; and (c) The library user's "library literature" or the commitment to find time in keeping up to date in not very good. The following recommendations proposed to further improve current awareness services in Saint Louis University Library: (a) Bulletin board should include recent news of interest of library users, calendar of events, summary of recent events, annotated list of new books, table of contents, and abstracts of newly published and unpublished library materials; b) Technological advances should be introduced and utilized in commencing methods to library users in order to encourage members to make use of recent information; c) Newsletter, organized and written by the University Library should exist to keep the library user's readership up to date; d) ""Ball game"" technique can be used to increase the chance of journal routing wherein each client returns the issue to the library after reading it then sends the issue to the next client on the list. Six people on a circulation list are a useful maximum; (e) Provide comprehensive orientation on current awareness services to library users in terms of its functions and significance on their field of work, learning endeavor, research and other fields of interests; (f) Develop document delivery in order to be more responsive to the needs of the profession;(g)Librarians dedicated to supplying information to other members of the academe should be knowledgeable in information handling and disseminating; (h) For further study, inclusion of new methods of current awareness services in Saint Louis University Library and assessment of needs based on the different college departments.
Vita.
Thesis (Master of Library and Information Science)--University of the Philippines Diliman
Keywords: Current awareness services -- Philippines -- Baguio City; Library use studies -- Philippines -- Baguio City